READING DIFFICULTIES: COMPARISON ON STUDENTS’AND TEACHERS’ PERCEPTION - Fernandita Gusweni Jayanti (Proceedings of ISELT FBS Universitas Negeri Padang, 2016)
There have been plenty studies conducted in order to find and develop the best techniques and strategies to help improving students’ reading comprehension. Those teaching techniques and strategies were mostly developed based on teachers’ work on existing the theories and framework. However, amid the development and practices of these techniques and strategies, students’ perceptions towards the teaching and learning process get less attention. Therefore, this study tries to bring the light into students’ perceptions. This study aimed to examine and compare students’ and teachers’ perception regarding students’ reading difficulties. Through random sampling, 80 students of English Department at the University of Bengkulu were chosen to fill a questionnaire. The questionnaire was developed based on reading macro and micro skills to investigate students’ reading difficulties. The similar questionnaire was also given to 4 lecturers who teach reading courses in the department. Some students and teachers were also interviewed to clarify some information or to get more elaboration about some interesting points. The results of the study showed that students and teachers’ agree in some points and showed different perceptions in some points. The finding of this study will be a good reflection for the teachers as well as for the students on their reading activities in the classroom. Furthermore, it is helpful for the teachers in their efforts to develop better program for reading classes to improve students’ reading comprehension.